Reconstructing Higher Education Perceptions amid the Strengthening of Non-Academic Success Narratives among Indonesian Youth - Zulfikar (Islamic Studies and Education Journal, 2026)
The rapid development of social media has strengthened the dissemination of non-academic success narratives that position wealth, popularity, and entrepreneurial achievement as primary indicators of success. Although numerous studies have examined the relationship between education, social mobility, and youth aspirations, limited attention has been given to how these narratives shape perceptions of higher education among Indonesian youth. This study aims to analyze the shifting meaning of higher education among Indonesian youth and reconstruct its role within the framework of human development and social progress. This research employed a narrative literature review using a sociology of education perspective. A total of 45 academic sources, including journal articles, scholarly books, policy reports, and publications from national and international institutions, were analyzed through qualitative content analysis. The findings indicate that the growing prominence of non-academic success narratives has shifted educational orientation from intellectual and character development toward short-term economic considerations. Higher education is increasingly evaluated through a cost-benefit perspective and compared with alternative pathways to success perceived as faster and more practical. The novelty of this study lies in the integration of educational sociology and digital culture perspectives to explain the changing social meaning of higher education in contemporary society. The findings emphasize the importance of reconstructing higher education as a means of developing competencies, critical thinking, and social responsibility in the digital era.